2021
DOI: 10.1186/s12866-021-02311-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mulberry leaf silage on antioxidant and immunomodulatory activity and rumen bacterial community of lambs

Abstract: Background Rumen is a natural fermentation system and the microorganisms inside can effectively utilize plant bioresource and interact with host metabolism. Here, analysis of rumen microbiome, together with animal performance and serum metabolism in a lamb model were performed to identify the potential use of mulberry leaf silage (MS) to replace alfalfa silage (AS) as a new functional feed resource and to mining the novel specific mulberry leaf associated rumen bacteria interact with host metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…A large number of studies have confirmed that adding mulberry silage to the diet can improve production performance [ 18 ], enhance the antioxidant capacity [ 19 ], improve meat quality [ 13 ] and increase economic benefits [ 20 ]. At the same time, it plays an important role in maintaining ruminant health and changing the rumen bacterial-community structure [ 21 ]. However, it has not been fully utilized as feedstuff for ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have confirmed that adding mulberry silage to the diet can improve production performance [ 18 ], enhance the antioxidant capacity [ 19 ], improve meat quality [ 13 ] and increase economic benefits [ 20 ]. At the same time, it plays an important role in maintaining ruminant health and changing the rumen bacterial-community structure [ 21 ]. However, it has not been fully utilized as feedstuff for ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of creatinine, total cholesterol (T-CHO), blood urea nitrogen (BUN), the activities of total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) in serum were determined by commercial kits (Jiancheng Biological Technology Co., Ltd., Nanjing, China) by following the manufacturer’s instructions [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The application of plants or their extracts as feed components or feed additives has also been evaluated in sheep and goats ( Table 3 ). In a previous study, a diet with mulberry leaf silage as a new feed resource, replacing alfalfa silage, improved the antioxidant capability and immunity of lambs and correspondingly enhanced their health by enhancing the abundance of Bifidobacterium and Lactobacillus in the rumen while inhibiting Ruminococcaceae UCG-010 and Lachnospiraceae_XPB1014 group [ 105 ]. These beneficial effects were attributed to the mulberry leaf’s content of polyphenols and polysaccharides, as these bioactive compounds can mitigate inflammation processes by enhancing serum IFN-γ levels and influencing the microbiota [ 106 ].…”
Section: Application Of Plant Extracts In Ruminantsmentioning
confidence: 99%